EVALUASI USER EXPERIENCE PADA APLIKASI WONDR BY BNI MENGGUNAKAN METODE UEQ DAN SUS - Indah Lestari; Eki Saputra; M Afdal; Febi Nur Salisah; Syaifullah Syaifullah (Program Studi Sistem Informasi, Universitas Banten Jaya, 2025)
Wondr by BNI is a mobile banking application in Indonesia designed to support systematic financial management through three main concepts: Insight, Transaction, and Growth. Despite offering advanced features, many users complain about issues such as failed transactions, login difficulties, and slow application response times. This study evaluates the user experience of the Wondr app by combining the UEQ and SUS methods. The UEQ evaluation results show an average score of: attractiveness 1.12; clarity 1.06; efficiency 1.05; accuracy 1.07; stimulation 0.71; and novelty 0.77. Meanwhile, the SUS score of 64.6 falls into category D, “OK” on the adjective scale, and “Marginally Acceptable” on the usability scale—indicating that the app's usability is slightly below the average standard. Overall, users gave positive ratings for clarity, efficiency, accuracy, and stimulation, but attractiveness and novelty still need improvement. To date, no studies have specifically evaluated the UX of the Wondr app by combining the UEQ and SUS methods. This research contributes new scientific insights by demonstrating the app's UX performance and areas requiring improvement.